Effects of Thermal and Acidic Treatments on the Characteristics of Algerian Bentonite - Lahmek, Mohamed; Aziz Ramadan, Abdul (Asian Journal of Chemistry, 2010)
The natural and treated Algerian bentonites were studied using different methods such as chemical analysis, thermal analysis, X-ray diffraction, infrared absorption and nitrogen adsorption, to determine their constituents and to characterize the effect of treatment on their superficial structures and textural properties. Results show that the natural bentonite is composed essentially of montmorillonite, quartz and a small quantity of albite. The natural material was thermally treated at 650 and 1100ºC, then refluxed with 6 N HCl (B650 and B 1100). The B650 sample is composed of quartz, albite, spinel and a small quantity of keatite. The B1100 sample is composed of cristobalite, spinel and a small quantity of quartz. The surface areas (SBET) and the total pore volumes are decreased with raising the temperature of thermal treatment (SB600 = 160 m2/g, SB650 = 112 m2/g, SB750 = 50 m2/g, SB850 = 24 m2/g, SB950 = 17 m2/g, SB1000 = 13 m2/g and SB1100 = 12 m2/g).